The relationship between corporate governance and firm performance: An empirical analysis of Indonesian companies - Husnah Husnah; Aryati Aryati; Ramlawati Ramlawati; Mochammad Fahlevi (Privietlab, 2023)
The goal of this study is to investigate the relationship between corporate governance practices, as indicated by the Corporate Governance Perception Index (CGPI) scores, and key performance indicators (ROA, ROE, EPS) of publicly-listed Indonesian firms. Utilizing a panel data set comprising 112 Indonesian firms across various sectors, both fixed and random effects models were employed to discern the effects of corporate governance on firm performance. The dataset spanned five years, resulting in a total of 560 observations. The findings revealed a positive and statistically significant correlation between superior governance practices and enhanced firm performance. Specifically, a one-unit increase in the CGPI Score corresponded with increases in ROA, ROE, and EPS, even after controlling for variables such as firm size and industry type. Corporate governance plays a pivotal role in influencing the financial performance of Indonesian firms. Firms adhering to higher governance standards showcased better performance metrics, underscoring the strategic importance of robust governance mechanisms in the Indonesian business landscape. The results hold significant implications for Indonesian businesses, investors, and policymakers. Effective governance practices not only serve as a beacon for potential investors but also position firms for sustained growth and stakeholder trust in an increasingly competitive and interconnected global economy.